Electron transfer rate analysis of a site-specifically wired copper oxidase - Schlesinger, Orr; Pasi, Mor; Dandela, Rambabu; Meijler, Michael M.; Alfonta, Lital (Physical Chemistry Chemical Physics, 2018)
Electron transfer kinetic parameters of site-specifically wired copper oxidase were investigated. The enzyme's orientation towards the electrode was controlled by incorporation of propargyl-L-lysine as a site-specific anchoring point. Herein, we demonstrate the importance of immobilization orientation and how it affects electron transfer efficiency and kinetics to each of the enzyme's two active sites.